1990
DOI: 10.1007/bf01662781
|View full text |Cite
|
Sign up to set email alerts
|

Die prognostische Bedeutung von Lymphozytensubpopulationen und Makrophagen im peripheren Blut und in der bronchoalveolären Lavage bei AIDS-Patienten mit Verdacht auf Pneumocystis-carinii-Pneumonie

Abstract: In 36 HIV seropositive patients with the clinical manifestation of AIDS and a suspected Pneumocystis carinii infection, lymphocyte subpopulations were analyzed in the peripheral blood (PBL) and compared with the results of the bronchoalveolar lavage (BAL). Of those 36 patients, 29 showed a highly abnormal CD4/CD8 ratio in both the PBL and the BAL. The clinical course of these 29 patients was unpredictable. In seven patients, however, the CD4/CD8 ratio in the BAL was normal or only slightly altered, despite a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Fleury et al (7) further showed that alveolar macrophages are 69.5% of the total cell population in bronchoalveolar lavage (BAL) fluids from immunocompromised patients without PCP but are only 38.8% of the total cell population in BAL fluids from PCP patients with AIDS. The reduction in alveolar macrophage number was found in both human immunodeficiency virus-positive and -negative patients with PCP but was not observed in either human immunodeficiency virus-positive or -negative patients without PCP (7,11). A similar observation was reported by Sadaghdar et al (28), i.e., that alveolar macrophages account for 64% of total cells in BAL fluids from AIDS patients without PCP and only 45% in BAL fluids from AIDS patients with PCP.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…Fleury et al (7) further showed that alveolar macrophages are 69.5% of the total cell population in bronchoalveolar lavage (BAL) fluids from immunocompromised patients without PCP but are only 38.8% of the total cell population in BAL fluids from PCP patients with AIDS. The reduction in alveolar macrophage number was found in both human immunodeficiency virus-positive and -negative patients with PCP but was not observed in either human immunodeficiency virus-positive or -negative patients without PCP (7,11). A similar observation was reported by Sadaghdar et al (28), i.e., that alveolar macrophages account for 64% of total cells in BAL fluids from AIDS patients without PCP and only 45% in BAL fluids from AIDS patients with PCP.…”
supporting
confidence: 61%
“…Several studies in the 1980s and 1990s showed that the number of alveolar macrophages in BAL fluid from AIDS patients with PCP was reduced relative to other cell types (7, 8, 11,42,44). It was unknown whether this change is due to a decrease in the number of alveolar macrophages or an increase in other cell types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pneumocystis carinii ( P. carinii ) remains a major cause of pneumonia in patients with AIDS as well as other immunocompromised patients [3,5]‐ Alveolar macrophages are important for the clearance of P. carinii. Previous reports state that alveolar macrophage number in bronchoalveolar lavage (BAL) fluid, relative to other cell types, decreases during P. carinii pneumonia in immunosuppressed individuals [2,4,6]. Alveolar macrophages in immunosuppressed humans and animals are exposed to an altered immune environment, affecting their response to infectious agents.…”
mentioning
confidence: 99%